Identification of Glycoside Transporters From the Human Gut Microbiome - Wang, Zhi; Tauzin, Alexandra S.; Laville, Elisabeth; Potocki-Veronese, Gabrielle (Frontiers in Microbiology, 2022)
Transport is a crucial step in the metabolism of glycosides by bacteria, which is itself key for microbiota function and equilibrium. However, most transport proteins are function-unknown or only predicted, limiting our understanding of how bacteria utilize glycosides. Here, we present an activity-based screening method to identify functional glycoside transporters from microbiomes. The method is based on the co-expression in Escherichia coli of genes encoding transporters and carbohydrate-active enzymes (CAZymes) from metagenomic polysaccharide utilization loci (PULs) cloned in fosmids. To establish the proof of concept of the methodology, we used two different metagenomic libraries derived from human gut microbiota to select 18 E. coli clones whose metagenomic sequence contained at least one putative glycoside transporter and one functional CAZyme, identified by screening for various glycoside-hydrolase activities. Growth tests were performed on plant-derived glycosides, which are the target substrates of the CAZymes identified in each PUL. This led to the identification of 10 clones that are able to utilize oligosaccharides as sole carbon sources, thanks to the production of transporters from the PTS, ABC, MFS, and SusCD families. Six of the 10 hit clones contain only one transporter, providing direct experimental evidence that these transporters are functional. In the six cases where two transporters are present in the sequence of a clone, the transporters’ function can be predicted from the flanking CAZymes or from similarity with transporters characterized previously, which facilitates further functional characterization. The results expand the understanding of how glycosides are selectively metabolized by bacteria and offers a new approach to screening for glycoside-transporter specificity towards oligosaccharides with defined structures.